2022
DOI: 10.1093/ofid/ofac128
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Factors for Epstein-Barr Virus Reactivation in a High-Risk Area of Nasopharyngeal Carcinoma: A Population-Based Study

Abstract: Background Epstein-Barr virus (EBV) reactivation from latent to lytic infection has been considered as a key step in nasopharyngeal carcinoma oncogenesis. However, epidemiological evidence regarding environmental risk factors for EBV reactivation on a population level remains largely lacking. Methods We enrolled 1,916 randomly selected adults from the general population of Guangdong and Guangxi, China, from 2010 to 2014. Info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…EBV has been linked to a number of disorders. For example, both EBV replication and cigarette smoking have been shown to be associated with nasopharyngeal carcinoma occurring largely in China [ 16 ]. EBV has also recently been associated with autoimmune disorders such as multiple sclerosis [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…EBV has been linked to a number of disorders. For example, both EBV replication and cigarette smoking have been shown to be associated with nasopharyngeal carcinoma occurring largely in China [ 16 ]. EBV has also recently been associated with autoimmune disorders such as multiple sclerosis [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…One was a population‐based case‐control cohort (defined as cohort1), and the other was a hospital‐based case‐control cohort (defined as cohort2). Saliva of the cohort1 was from a collaborative study of NPC entitled “NPC genes, Environment, and EBV.” Details of the study were described previously 32,33 . Participants including 2554 NPC patients and 2648 controls were from 13 cities/counties in Guangdong Province and Guangxi Autonomous region in southern China between 2010 and 2014.…”
Section: Methodsmentioning
confidence: 99%
“…Details of the study were described previously. 32,33 Participants including 2554 NPC patients and 2648 controls were from 13 cities/counties in Guangdong Province and Guangxi Autonomous region in southern China between 2010 and 2014. Finally, 2350 (92.0%) and 2505 (94.6%) salivary samples were, respectively, collected from enrolled cases and controls.…”
Section: Patients and Controlsmentioning
confidence: 99%
“…Cigarette smoke extract promotes EBV replication and induces the expression of lytic genes in vitro . Epidemiological studies revealed the association of smoking with persistent reactivation of EBV, as reflected by elevated plasma levels of its antibodies, which increase the risk of carcinogenesis ( Xu et al, 2012 ; Chen et al, 2022 ).…”
Section: The Pathogenic Role Of Ebv In Npcmentioning
confidence: 99%